POSSIBILITIES FOR THE DEVELOPMENT OF RURAL TOURISM IN THE REPUBLIC OF MACEDONIA - Koteski, Cane; Majhošev, Darko; Jakovljev, Zlatko (Journal of process management and new technologies, 2017)
Rural tourism as part of the overall tourist offer in Macedonia is currently booming. Almost every tourist offer of all the travel agencies contains, among other things, visiting interesting rural tourist areas. This kind of tourism is an important alternative form of tourism that offers a higher level of meeting modern man’s needs that urban lifestyle is not able to satisfy. The dynamic and stressful life in urban areas contributes to people seeking peaceful areas that are far from urban centers which, with their natural potentials, offer the modern and somewhat tired man quality contents for relaxing and resting. These are rural areas that are identified with certain geographical regions possessing natural beauty, historic sights and cultural events that are an important factor for the development and promotion of rural tourism. Modern entrepreneurs perceive rural tourism as economic development of rural areas which brings significant revenues for families dealing with this kind of tourism, and also as a significant factor in keeping the population in these rural areas. The paper contains conceptual determination and definition of rural tourism, rural tourism types, and retains the profile of rural tourism visitors. The second part of the paper analyzes the situation with rural tourism in Macedonia, especially the legal framework for the development of rural tourism, institutional framework, human resources, accommodation and catering facilities, funding opportunities, promotional activities, etc.